2016
DOI: 10.1056/nejmra1404711
|View full text |Cite
|
Sign up to set email alerts
|

Renal Complications of Hematopoietic-Cell Transplantation

Abstract: ach year, approximately 50,000 patients worldwide undergo hematopoietic-cell transplantation. This procedure, which is used to treat a wide range of malignant and nonmalignant diseases, may involve either a myeloablative or reduced-intensity conditioning regimen; the use of alternative allogeneic donors (i.e., haploidentical or mismatched donors); cells from bone marrow, cord blood, or peripheral-blood stem cells; and new immunomodulatory agents to prevent graft-versus-host disease (GVHD) 1 (Table 1). Despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
177
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(192 citation statements)
references
References 98 publications
(74 reference statements)
3
177
1
1
Order By: Relevance
“…According to a recent report, kidney-biopsy specimens obtained from patients with TMA showed mesangiolysis and loss of endothelial cells with occlusion of capillary lumens with fibrin, as was the case for our patient [13]. According to one institution's study of 67 patients, kidney specimens often demonstrated acute tubular injury, interstitial fibrosis, arteriolar hyaline, arteriosclerosis, and rarely membranous nephropathy [25].…”
Section: Renal Pathology In Gvhd and Ta-tmasupporting
confidence: 73%
See 3 more Smart Citations
“…According to a recent report, kidney-biopsy specimens obtained from patients with TMA showed mesangiolysis and loss of endothelial cells with occlusion of capillary lumens with fibrin, as was the case for our patient [13]. According to one institution's study of 67 patients, kidney specimens often demonstrated acute tubular injury, interstitial fibrosis, arteriolar hyaline, arteriosclerosis, and rarely membranous nephropathy [25].…”
Section: Renal Pathology In Gvhd and Ta-tmasupporting
confidence: 73%
“…Chronic kidney disease is estimated to impact 15-20% HSCT recipients [22]. Acute injury is considered to occur when serum creatinine levels are elevated up to 100 days after transplantation, whereas chronic injury represents injury at or after that [13]. This was the case for our patient who presented with a decline in renal function, more than a year after her transplant.…”
Section: Renal Pathology In Gvhd and Ta-tmamentioning
confidence: 90%
See 2 more Smart Citations
“…[3][4][5][6] However, GvHD as a severe inflammatory disease may also indirectly cause nephropathy. 7 The exact etiology of renal dysfunction after BMT often remains unclear, because no renal biopsy is taken in most cases. However, AKI is a risk factor for developing chronic kidney disease (CKD) and is associated with increased morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%